Fidelio : an opera in two acts, the music by Beethoven ; the libretto, with new recitatives, arranged by Manfredo Maggioni ; as represented at the Royal Italian Opera, Covent Garden. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Sonnleithner, Joseph Ferdinand, 1766-1835 (librettist):::Contributor::::::::::::; Breuning, Stephan von (librettist):::Contributor::::::::::::; Treitschke, Georg Friedrich, 1776-1842 (librettist):::Contributor::::::::::::; Royal Italian Opera (London, England)::::::::::::::: (United Kingdom; London; T. Brettell, 2022)
Libretto of Fidelio for performances at the Covent Garden in 1851, conducted by Michael Costa, including cast let and stage directions.